Dampak Bulying Pada Psikologi Anak Usia Dini Dan Progam Pencegahan Pemerintah - Nuri Arifiah Romadhoni (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Bullying is a form of abuse or violence, which is carried out directly by one person or a stronger group. Bullying is bullying that is carried out physically against others and is carried out continuously, bullying is bullying that is carried out repeatedly by stronger actors against weaker actors, carried out deliberately and carried out to complete their tasks physically and emotionally. "Bullying is any form of oppression or violence, perpetrated intentionally by a stronger person or group. The purpose of bullying is to hurt others and is done continuously."Bullying is an act of intimidation carried out repeatedly by a stronger party against a weaker party, carried out deliberately and with the aim of hurting the victim physically and emotionally.